International financial integration and economic growth in developed and developing countries - Ibrahim, Saifuzzaman (National Academy of Management, 2011)
This paper aims to investigate the impact of international financial integration (IFI) on economic growth in developed and developing countries. Using dynamic panel model analysis, findings show that the impact of IFI is different between the two groups of countries. The presence of IFI in developing countries has a positive impact on economic growth while no significant relationship between these two variables is found in developed countries.